Agricultural by-products for building insulation: Acoustical characterization and modeling to predict micro-structural parameters. (1st June 2016) - Chabriac, P.A.; Gourdon, E.; Gle, P.; Fabbri, A.; Lenormand, H.
Highlights: Study of agricultural by-products available for acoustical applications. Characterization of five types of agricultural by-products acoustically and structurally. Measurements and modelings of sound absorption. Prediction of micro-structural parameters. Abstract: The acoustical characteristics for building insulation of five largely available plant particles (hemp shiv, sunflower bark and pith, flax shiv and rape straw) without binder were investigated. Results show that they can all be used for acoustical absorption. Measurements were then analyzed to estimate not only the sound absorption coefficient, but also the particles intrinsic properties such as porosities (i.e. total, inter- and intra-particles porosities) and densities (i.e. bulk and skeletal). An equivalent fluid model is then used to predict the sound absorption. From acoustical measurements, simple analytical equations allow to estimate key micro-structural parameters such as tortuosity, viscous and thermal characteristic lengths and resistivity.